FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA IBU HAMIL - Ashari, Elva Febri; Mahardika, Putri; Primasari, Yefta; Noviasari, Damai; Herniyatun, Herniyatun (Ensiklopedia of Journal, 2024)
Hypertension in pregnancy is a medical condition that often occurs during pregnancy and can cause complications in 2-3% of pregnancy. Based on the author's preliminary survey in the form of document searches and initial interviews with pregnant women, it is known that most pregnant women who experience hypertension are aged <20 and ≥35 years. The research objective was to determine the factors associated with the incidence of hypertension in the working area of Puskesmas Payung Sekaki, Pekanbaru City in 2020. This research is quantitative observational analytic with cross sectional design on a sample of 74 people in the working area of Puskesmas Payung Sekaki using consecutive sampling technique. . Univariate and bivariate data analysis used the Chi Square Test. The results showed that there was a relationship between age (p value = 0.046, POR = 3.686), history of hypertension (p value = 0.004, POR = 5.384), parity (p value = 0.009, POR = 5.238), consumption of vegetables and fruit (p value = 0.016, POR = 3.889), risky foods (p value = 0.037, POR = 3.267), while the role of health workers was not related (p value = 0.106, POR = 0.407) and exposure to cigarette smoke (p value = 0.221, POR = 0.394 ). The conclusion of the study is that there is a relationship between age variables, history of hypertension, parity, consumption of vegetables and fruits, risky foods with the incidence of hypertension in pregnant women in the working area of Puskesmas Payung Sekaki in 2020. It is recommended that Payung Sekaki Puskesmas should monitor the evaluation of the Non-communicable Diseases program in particular. Hypertension in pregnant women and optimizing efforts to prevent hypertension CERDIK for pregnant women.Keywords: Hypertension, Age, Parity, History of hypertension